Statistical model for Plum pox virus prediction in Prunus nursery blocks using vector and virus incidence data in four different European ecological areas - Vidal, Eduardo; Zagrai, Luminita Antonela; Malinowski, Tadeusz; Soika, Grazyna; Warabieda, Wojciech; Tasheva-Terzieva, Elena; Milusheva, Snezhana; Zagrai, Ioan; Kamenova, Ivanka; Bozhkova, Valentina; Martínez, M. Carmen; Cambra-López, María; et al. (Wiley Online Library, 2020)
Plum pox virus (PPV) is the causal agent of sharka, the most devastating virus disease of Prunus species. PPV is transmitted by vegetative propagation, particularly by grafting, as well as by aphid species in a nonpersistent manner. The objective of this paper was to evaluate the prevalence and diversity of PPV‐vector aphid species in representative European areas of prunus cultivation. Four experimental nursery plots were established in Skierniewice (Poland), Liria (Spain), Plovdiv (Bulgaria) and Bistrita (Romania). Aphid population was weekly monitored using the sticky shoot method in spring and/or autumn in each nursery plot. Furthermore, we estimated the relative efficiency factor for the main PPV‐vector aphid species using bibliographic and reference data. Aphid diversity in each nursery plot was assessed using the Shannon index and the number of estimated aphid species was calculated by the rarefaction method. The highest diversity of aphid species population was reported in Plovdiv in spring while the lowest diversity was found in Liria in spring. A cluster analysis based on Morisita–Horn similarity index was performed to study the differences in species composition between the four nursery plots and seasons. Aphid population was clearly grouped by location and season. Results showed Aphis spiraecola and Hyalopterus pruni complex were typically spring aphid species, while Anoecia corni and Rhopalosiphum padi dominated autumn catch. Regarding PPV‐vector aphid species present in nursery plots, A. spiraecola was the most prevalent PPV‐vector aphid species in Liria and in Bistrita, showing a high relative efficiency factor of PPV transmission (0.91). Consequently, A. spiraecola should be considered a key actor in the spread of PPV in these regions. Hyalopterus pruni complex was the most prevalent PPV‐vector aphid species in Skierniewice and Plovdiv, showing a very low relative efficiency factor of PPV transmission (0.09). Therefore, the role of H. pruni complex in spread of PPV in these regions can be considered negligible. Furthermore, we statistically demonstrated that the presence of specific PPV‐vector aphid species is associated with the spread of the disease, whereas the biodiversity of aphid species population does not affect the spread of PPV. Finally, the advantages of the use of vector pressure index in the management of sharka disease are discussed